The The Impact of Social Media, Peers, and Economic Knowledge on the Consumptive Behavior of Economic Students at Cenderawasih University. - Somisu, Rut Penina; Harikedua, Alfani Laura (Accounting Profession Journal (APAJI), 2025)
This study investigates the influence of social media, peer groups, and economic knowledge on the consumptive behavior of economics students at Cenderawasih University. In an era dominated by digital connectivity, young adults are increasingly exposed to consumption-driven content and social pressures that shape their financial habits. Using a mixed-method approach with stratified random sampling of 264 students, data were collected through validated questionnaires and analyzed using SPSS 30. The findings reveal that both social media usage and peer influence have a statistically significant and positive effect on students' consumptive behavior, while economic knowledge, although important, does not show a significant mitigating effect in this context. The results highlight that external social factors exert a stronger impact on student spending patterns than individual financial literacy. Consequently, the study suggests that interventions aimed at reducing impulsive consumption among students should prioritize managing social influences and fostering peer-led financial education initiatives, alongside strengthening the practical application of economic knowledge in academic settings.